Norms for Automatic Estimation of Hippocampal Atrophy and a Step Forward for Applicability to the Italian Population - De Francesco, Silvia; Galluzzi, Samantha; Vanacore, Nicola; Festari, Cristina; Rossini, Paolo Maria; Cappa, Stefano F.; Frisoni, Giovanni B.; Redolfi, Alberto (Frontiers in Neuroscience, 2021)
Introduction: Hippocampal volume is one of the main biomarkers of Alzheimer's Dementia (AD). Over the years, advanced tools that performed automatic segmentation of Magnetic Resonance Imaging (MRI) T13D scans have been developed, such as FreeSurfer (FS) and ACM-Adaboost (AA). Hippocampal volume is considered abnormal when it is below the 5th percentile of the normative population. The aim of this study was to set norms, established from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) population, for hippocampal volume measured with FS v.6.0 and AA tools in the neuGRID platform (www.neugrid2.eu) and demonstrate their applicability for the Italian population. Methods: Norms were set from a large group of 545 healthy controls belonging to ADNI. For each pipeline, subjects with segmentation errors were discarded, resulting in 532 valid segmentations for FS and 421 for AA (age range 56-90 years). The comparability of ADNI and the Italian Brain Normative Archive (IBNA), representative of the Italian general population, was assessed testing clinical variables, neuropsychological scores and normalized hippocampal volumes. Finally, percentiles were validated using the Italian Alzheimer’s disease Repository Without Borders (ARWiBo) as external independent data set to evaluate FS and AA generalizability. Results: Hippocampal percentiles were checked with the chi-square goodness of fit test. P-values were not significant, showing that FS and AA algorithm distributions fitted the data well. Clinical, neuropsychological and volumetric features were similar in ADNI and IBNA (p>0.01). Hippocampal volumes measured with both FS and AA were associated with age (p<0.001). The 5th percentile thresholds, indicating left/right hippocampal atrophy were respectively: (i) below 3223/3456 mm3 at 56 years and 2506/2415 mm3 at 90 years for FS; (ii) below 4583/4873 mm3 at 56 years and 3831/3870 mm3 at 90 years for AA. The average volumes computed on 100 cognitively intact healthy controls (CN) selected from ARWiBo were close to the 50th percentiles, while those for 100 AD patients were close to the abnormal percentiles. Discussion: Norms generated from ADNI through the automatic FS and AA segmentation tools may be used as normative references for Italian patients with suspected AD.